The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0cc05999d
|View full text |Cite
|
Sign up to set email alerts
|

Dual H-bond activation of NHC–Au(i)–Cl complexes with amide functionalized side-arms assisted by H-bond donor substrates or acid additives

Abstract: Novel approach with amide-tethered H-bond donor NHC ligands enabled Au(I)-catalysis via H-bonding. The plain NHC-Au(I)-Cl complex catalysed conversions of terminal N-propynamides to oxazolines, and enyne cycloisomerization with an acid additive,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 28 publications
(17 reference statements)
2
37
0
Order By: Relevance
“…It was found that chloride abstraction occurs with a remarkable low barrier of 6.7 kcal/mol, via an associative ligand exchange mechanism, wherein the displaced chloride ion is stabilized by a triple H‐bond established with the two NH groups of the squaramide and the NH functionality of amide 12 a . Helaja and coworkers computed a very similar mechanism for the Au−Cl bond activation of a NHC−Au(I) chloride complex possessing a pendant tosylamide, finding a 13.2 kcal/mol barrier with their system [13] . Therefore, computations suggest that the bidentate HBD on complex 1 facilitates the chloride abstraction step.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…It was found that chloride abstraction occurs with a remarkable low barrier of 6.7 kcal/mol, via an associative ligand exchange mechanism, wherein the displaced chloride ion is stabilized by a triple H‐bond established with the two NH groups of the squaramide and the NH functionality of amide 12 a . Helaja and coworkers computed a very similar mechanism for the Au−Cl bond activation of a NHC−Au(I) chloride complex possessing a pendant tosylamide, finding a 13.2 kcal/mol barrier with their system [13] . Therefore, computations suggest that the bidentate HBD on complex 1 facilitates the chloride abstraction step.…”
Section: Resultsmentioning
confidence: 98%
“…The reaction was found to be faster for more electron‐rich substrates, while it required more than 24 h to reach completion with electron‐poor amides 12 c and 12 d . Whereas electronic variations on the standard substrate 12 were tolerated, complexes 1 – 5 , 8 b and 9 b did not to catalyze the silver‐free cyclizations of N ‐(but‐3‐yn‐1‐yl)benzamide, bearing a homopropargylic substituent, and of the less reactive [13,25] N ‐(3‐phenylprop‐2‐yn‐1‐yl)benzamide possessing an internal alkyne [29] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations